2014
DOI: 10.1159/000362920
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Components and Subclinical Cerebrovascular Disease in the Northern Manhattan Study

Abstract: Background: Subclinical cerebrovascular disease has been associated with multiple adverse events related to aging, including stroke and dementia. The modifiable risk factors for subclinical cerebrovascular disease beyond hypertension have not been well characterized. Our objective was to examine the association between baseline, and changes over time, in lipid profile components and subclinical cerebrovascular disease on magnetic resonance imaging (MRI). Methods: Fasting plasma lipids were collected on partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
3
24
1
Order By: Relevance
“…This finding supports the report that age is the most important risk factor in developing cardiovascular or heart diseases [11]. It also correlates with data obtained from a study done on stroke patients in Northern Manhattan where the mean age was 68.8% [12]. Multiple explanations have been proposed to explain why age increases the risk of cardiovascular/heart diseases.…”
Section: Discussionsupporting
confidence: 90%
“…This finding supports the report that age is the most important risk factor in developing cardiovascular or heart diseases [11]. It also correlates with data obtained from a study done on stroke patients in Northern Manhattan where the mean age was 68.8% [12]. Multiple explanations have been proposed to explain why age increases the risk of cardiovascular/heart diseases.…”
Section: Discussionsupporting
confidence: 90%
“…The key limitation of the study was that the depth of vascular ascertainment was shallow. ADNI does not actively recruit participants with high vascular risk burden, so we did not have the statistical power to detect effects of vascular risk as other studies with larger sampling of these conditions have demonstrated ( Hughes et al, 2012 ; de Bruijn et al, 2014 ; Willey et al, 2014 ; Geijselaers et al, 2015 ). Advanced assays and more in-depth documentation of vascular history would provide a more precise characterization of current vascular status and may have provided a clearer picture of which specific processes may be involved in the development of WMHs.…”
Section: Discussionmentioning
confidence: 99%
“…The processing of MRI scans to quantify white matter hyperintensity and cerebral, lateral ventricular, and intracranial volumes, and to identify subclinical brain infarcts, has been described previously. 27 Assessment of LTPA. LTPA was measured using an in-person questionnaire adapted from the National Health Interview Survey of the National Center for Health Statistics.…”
Section: Methods Recruitment Of the Cohort The Northernmentioning
confidence: 99%